Benign, Malignant or Something in Between: A Rapidly Developing Atypical Parathyroid Adenoma - Sykja, Albana (J Endocr Soc, 2021)
Introduction: Although Primary Hyperparathyroidism (PHPT) is the third most common endocrine disorder, parathyroid carcinoma and atypical parathyroid adenoma are the rarest of endocrine tumours. The true incidence of atypical parathyroid adenomas has been elusive to endocrinologists since it is not possible to differentiate clinically between parathyroid carcinoma and atypical parathyroid adenomas before histological analysis. Atypical parathyroid adenoma represents a group of an intermediate form of parathyroid neoplasms with uncertain malignant potential. The majority of patients present with hypercalcaemia, however the development of atypical adenoma in patients with known PHPT is extremely rare. Clinical Case: A 78-year-old gentleman presented at the emergency department with lethargy and slurred speech which had started 1 week ago. Blood tests revealed severe hypercalcaemia. (Ca 4.98 mmol/L, PTH 114.2 pmol/L). The patient had a background of primary hyperparathyroidism which was diagnosed due to incidental mild hypercalcaemia (Ca 2.71 mmol/L, PTH 17.57 pmol/L, 25OH-vitamin D3 55 nmol/L). 2 weeks prior to presentation to the Emergency Department calcium and PTH levels were stable. On clinical examination, he was found mildly confused with no other clinical findings. No precipitating factors were identified. Hydration with IV crystalloids commenced and bisphosphonate IV was given. In view of PHPT Cinacalcet was added to treatment (30 mg BD). While the calcium levels seemed to improve initially, (lowest level achieved Ca 3.05 mmol/L) a week later they started to rise gradually. Hypercalcaemia proved refractory to medical treatment despite concomitant use of aggressive hydration, increased cinacalcet dose, second intravenous bisphosphonate, and intravenous calcitonin. Neck U/S revealed a probable parathyroid adenoma measuring 2cm axially at the inferior pole of the left thyroid lobe. In view of the severity and refractory nature of hypercalcaemia, a PET CT was requested which identified an 18 mm soft tissue mass in the left lower neck posterior to the left thyroid lobe with moderate to intense FDG uptake. There was no evidence of increased uptake elsewhere. The patient required 2 sessions of haemodialysis to maintain calcium levels around 3.5 preoperatively. He underwent parathyroidectomy with histological findings in keeping with atypical parathyroid adenoma. Gradual reduction of calcium levels was noted post-operatively with the lowest on day 10 (1.99) when he was started on oral calcium supplementation. The patient remains under follow-up with normal calcium levels 6 months postoperatively while remains on calcium and vitamin D3 supplements. Conclusion: To our knowledge, this is the only case of a patient with known primary hyperparathyroidism and mild hypercalcaemia, to develop severe parathyroid crisis with refractory to medical management hypercalcaemia within 2 weeks. Prompt surgical intervention remains of paramount importance in the management of these patients. They should have lifelong follow up in the view of uncertain malignant potential of the atypical parathyroid adenoma.